Operationalizing the One Heath approach : the global governance challenges - Lee, K. (2013)
Presents the One Health approach which calls upon the human, animal and environmental health sectors to cross professional, disciplinary and institutional boundaries, and to work in a more integrated way. Notes that while there has been wide-ranging commitment to this initiative, its operationalisation has proven challenging. Argues that work is hindered by dysfunctions characterising current forms of global health governance (GHG), viz., institutional proliferation, fragmentation, competition for scarce resources, lack of an overarching authority, and donor-driven vertical programmes.